THE EFFECT OF E-HEALTH EDUCATION MODULE AND BOOKLETS ON UNDERSTANDING OF CORONARY HEART DISEASE RISK PREVENTION IN ADOLESCENT IN THE COVID-19 PANDEMIC ERA - Farida halis; Sri Winarni; Fiashriel lundy; Siti Asiyah (Health Notions, 2023)
9.4 million deaths per year are caused by cardiovascular disease and 45% are caused by coronary heart disease (World Statistics). The prevalence of heart disease in Indonesia in 2018 nationally was 1.5% per population. The prevalence of heart disease in East Java is 1.6%, which is above the national prevalence of 1.5% (Riskesdas, 2018). To see the effectiveness of understanding and behavior in preventing the risk of coronary heart disease in adolescents (12-19 years), researchers are interested in conducting research on the effect of the booklet module and E-Health Education on the risk of coronary heart disease in adolescents (12-19 years). Keywords: e-health education module; booklets; prevention; coronary heart disease